A high performance metal-based heat-resistant composite material and preparation method thereof

By using silicon-doped boron quantum dots and modified carbon nanotubes as reinforcements in high-performance metal-based heat-resistant composite materials, the problem of poor mechanical properties of high-thermal conductivity composite materials in the prior art is solved, and the mechanical properties of the materials are realized and the significant improvement of heat resistance has expanded its application range.

CN118600273BActive Publication Date: 2025-01-07QINGDAO HAIYUAN CARBONE ALUMINUM ALLOY NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410393772.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-02
Publication Date
2025-01-07
Estimated Expiration
2044-04-02

AI Technical Summary

Technical Problem

The mechanical properties of existing highly thermal composite materials are poor, which limits their application range, especially in high temperature environments.

Method used

70-85 wt% copper powder, 5-20 wt% nickel powder, 1-5 wt% silver powder and 5-10 wt% silicon-doped boron quantum dots or silicon-doped boron quantum dots as reinforcements, and ultrasonic stirring and hydrothermal heat Silicon-doped boron quantum dots are prepared by reaction and combined with modified carbon nanotubes to form a high-performance metal-based heat-resistant composite material.

Benefits of technology

It significantly improves the mechanical properties and thermal conductivity of the material, improves the mechanical properties, enhances the stability and heat resistance of the material in high temperature and high stress environments, and expands its application range.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-performance metal-based heat-resistant composite material and a preparation method thereof, and belongs to the technical field of composite materials. The invention comprises the following raw materials by mass fraction: 70-85wt% copper powder, 5-20wt% nickel powder, 1-5wt% silver powder, and 5-10wt% reinforcement, wherein the reinforcement is silicon-doped boron quantum dots or silicon-doped boron quantum dot composites. The invention improves the wettability of the carbon-copper interface by adding silicon-doped boron quantum dot composites, improves the heat resistance and mechanical properties of the metal-based heat-resistant composite material, and effectively solves the problem of weak bonding when non-metallic nanomaterials are composited with metal substrates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a high-performance metal-based heat-resistant composite material and a preparation method thereof. Background Art

[0002] Metal matrix composites are made by combining particles, fibers or sheet reinforcements with high thermal conductivity and low thermal expansion coefficient with metals such as aluminum, copper, magnesium or silver. They integrate excellent physical properties such as high thermal conductivity and adjustable thermal expansion coefficient with mechanical properties of high stiffness, high strength and high toughness. They are the most competitive new thermal management materials in modern times.

[0003] High-performance metal-based heat-resistant composites are advanced materials with excellent thermal stability and mechanical properties. They are widely used in aerospace, energy and other engineering fields under high temperature environments. This type of composite material is usually composed of a metal matrix and a reinforcement to meet the stringent requirements for material performance under extreme high temperature conditions. The metal matrix usually uses a metal alloy with high melting point, high strength and high thermal conductivity, such as nickel-based alloys, titanium alloys or aluminum alloys. These metal matrices provide composite materials with excellent heat resistance and mechanical properties. Materials as reinforcements play a key role in high-performance metal-based heat-resistant composites. Common reinforcements include ceramic particles, carbon fibers, silicon carbide fibers, etc. These reinforcements can not only improve the strength and hardness of the material, but also improve its thermal expansion coefficient and thermal conductivity, so that the composite material performs well in high temperature environments.

[0004] Chinese invention patent CN 117187617 A discloses a high thermal conductivity composite material and a preparation method thereof. The high thermal conductivity composite material includes: a copper-based material and nitrogen-doped carbon quantum dots. The copper-based material and the nitrogen-doped carbon quantum dots are composited to form a high thermal conductivity composite material. The thermal conductivity of the high thermal conductivity composite material can reach above 458W / MK. However, the mechanical properties of the high thermal conductivity composite material prepared by the invention are poor, which greatly limits its application range. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a high-performance metal-based heat-resistant composite material and a preparation method thereof.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0007] A high-performance metal-based heat-resistant composite material comprises the following raw materials in mass fraction: 70-85wt% copper powder, 5-20wt% nickel powder, 1-5wt% silver powder, and 5-10wt% reinforcement, wherein the reinforcement is silicon-doped boron quantum dots or silicon-doped boron quantum dot composites.

[0008] Boron quantum dots have excellent hardness, strength and high thermal conductivity, so introducing them into metal-based heat-resistant composite materials can significantly improve the overall mechanical properties and thermal conductivity of the material, while the introduction of silicon can adjust the structure of quantum dots and increase their interaction with the metal matrix, thereby improving the overall mechanical properties of the material. The high hardness of silicon-doped boron quantum dots can effectively resist deformation and wear of materials under high temperature and high stress environments. This is for better dispersion and transfer of heat in high temperature environments, helping to slow down the temperature rise of the material and improve its heat resistance.

[0009] The method for preparing silicon-doped boron quantum dots comprises the following steps:

[0010] S1: mixing boron powder and N-methylpyrrolidone, stirring, ultrasonicating, and then adding a silane coupling agent and ultrasonicating to obtain a mixed solution;

[0011] S2: placing the above-mentioned mixed solution under nitrogen protection for hydrothermal reaction to obtain silicon-doped boron quantum dots.

[0012] However, silicon-doped boron quantum dots are not stable enough in the air, resulting in poor interface bonding performance with the metal matrix. Carbon nanotube materials have excellent mechanical properties and stability. Their introduction can not only significantly improve the mechanical properties of metal-based composites, but also improve the stability of boron quantum dots, which can effectively make up for the poor interface bonding performance between boron quantum dots and metal matrices. Therefore, they have become a reinforcement material widely used and studied in metal-based materials.

[0013] If carbon nanotubes are directly added to the copper matrix, the spatial distribution of the reinforcement is difficult to control due to the difference in the intrinsic properties of the carbon nanotubes and the matrix, resulting in unsatisfactory mechanical and heat resistance properties of the composite material. In order to obtain high-performance metal-based heat-resistant composite materials with excellent performance, it is necessary to overcome the problems of poor uniform dispersion of carbon nanotubes, poor C-Cu interface bonding, uncertain orientation of carbon nanotubes, and poor density of composite materials. Not only can it effectively combine with boron quantum dots to improve the interface bonding performance with the metal matrix, but it can also improve the bending strength, tensile strength, hardness, toughness and thermal conductivity of the material, so that the composite material can better resist the load under high temperature and high stress environment, reduce the risk of cracks and fractures under high stress, and significantly improve the thermal conductivity of metal-based composite materials.

[0014] The modified carbon nanotubes prepared by the present invention are fluid-like, so that the copper-based material and the silicon-doped boron quantum dots can be firmly combined through the B-Si-C-Cu bond in the pressing and calcining steps, and the silicon-doped boron quantum dots can be evenly dispersed in the copper-based material. In the subsequent processing and use process, the problem of distribution segregation of quantum dots can be reduced, and the use efficiency and stability are greatly improved. The effective boron quantum dots and modified carbon nanotubes of the present invention are effectively combined, each of which plays the role of heat resistance and mechanical properties. The interface of the modified carbon nanotubes and the Cu matrix generates internal stress, which is conducive to the good mechanical bonding between the composite interface. The introduced carbon nanotubes can improve the stability of the boron quantum dots in the metal-based heat-resistant composite material, and the boron quantum dots can be better dispersed in the metal-based composite material because of the combination with the carbon nanotubes, which improves the wettability between the reinforcing phase and the matrix, improves the interface bonding, and is conducive to improving the load transfer efficiency. The two synergize and enhance the heat resistance and mechanical properties of the metal-based heat-resistant composite material.

[0015] Preferably, the method for preparing silicon-doped boron quantum dots comprises the following steps:

[0016] S1: 8-14 parts by weight of boron powder and 60-160 parts by weight of N-methylpyrrolidone are mixed, stirred at 400-800 rpm for 20-50 min, ultrasonicated for 50-100 min at an ultrasonic power of 600-1000 W and an ultrasonic frequency of 60-100 kHz, and then 0.5-2 parts by weight of a silane coupling agent are added, and ultrasonicated for 3-6 h at an ultrasonic power of 600-1000 W and an ultrasonic frequency of 60-100 kHz to obtain a mixed solution;

[0017] S2: placing the above mixed solution under nitrogen protection, stirring at 160-220° C. and 400-800 rpm for 5-10 hours, cooling to room temperature, centrifuging, washing, and freeze-drying to obtain silicon-doped boron quantum dots.

[0018] The method for preparing the silicon-doped boron quantum dot composite comprises the following steps: S1 mixing boron powder and N-methylpyrrolidone, stirring, ultrasonicating, and then adding a silane coupling agent and ultrasonicating to obtain a mixed solution;

[0019] S2: adding modified carbon nanotubes to the above mixed solution and subjecting it to ultrasonic treatment, and then subjecting it to hydrothermal reaction under nitrogen protection to obtain a silicon-doped boron quantum dot composite.

[0020] Preferably, the preparation method of the silicon-doped boron quantum dot composite comprises the following steps: mixing 8-14 parts by weight of boron powder and 60-160 parts by weight of N-methylpyrrolidone, stirring at 400-800 rpm for 20-50 min, ultrasonicating at an ultrasonic power of 600-1000 W and an ultrasonic frequency of 60-100 kHz for 50-100 min, adding 0.5-2 parts by weight of a silane coupling agent, and ultrasonicating at an ultrasonic power of 600-1000 W and an ultrasonic frequency of 60-100 kHz for 3-6 h to obtain a mixed solution;

[0021] S2: Add 1-4 parts by weight of modified carbon nanotubes to the above mixed solution, ultrasonicate for 50-100 min at an ultrasonic power of 600-1000 W and an ultrasonic frequency of 60-100 kHz, then place under nitrogen protection, stir at 160-220° C. and 400-800 rpm for 5-10 h, cool to room temperature, centrifuge, wash, and freeze-dry to obtain a silicon-doped boron quantum dot complex.

[0022] The silane coupling agent is any one of 3-(methacryloyloxy)propyltrimethoxysilane, diethylenetriaminopropyltrimethoxysilane and 3-glycidyloxypropyltrimethoxysilane.

[0023] The method for preparing the modified carbon nanotubes comprises the following steps:

[0024] N1: graphitized carbon nanotubes, sodium nitrate and concentrated sulfuric acid are mixed and stirred, and potassium permanganate aqueous solution is added and stirred continuously; heating is performed for reaction, and hydrogen peroxide is added and stirred continuously to obtain defective carbon nanotubes;

[0025] N2 takes the above defective carbon nanotubes and water and ultrasonically obtains a dispersion of defective carbon nanotubes, and adds a hydroxy silicon derivative under heating and stirring to obtain pre-modified carbon nanotubes;

[0026] N3: Mix the pre-modified carbon nanotubes with water, disperse them by ultrasonic, filter and dry them, add the dried product into dichloromethane and surfactant and stir; let it stand, remove the upper clear liquid, retain the lower suspension, and dry it in vacuum to obtain modified carbon nanotubes.

[0027] Preferably, the method for preparing the modified carbon nanotubes comprises the following steps:

[0028] N1: 1-4 parts by weight of graphitized carbon nanotubes, 0.5-2 parts by weight of sodium nitrate, and 0.2-0.5 parts by weight of 98wt% concentrated sulfuric acid are mixed, stirred at 0°C and 200-600rpm for 15-30min, 15-30 parts by weight of 10-30wt% potassium permanganate aqueous solution are added, and stirring is continued for 0.5-2h; then stirred at 30-50°C and 50-200rpm for 20-40min, 30-80 parts by weight of water are added; then stirred at 80-100°C and 50-200rpm for 20-50min, 5-15 parts by weight of 20-35wt% hydrogen peroxide are added, stirring is continued for 10-30min, centrifuged, washed, and dried to obtain defective carbon nanotubes;

[0029] N2 takes 0.5-2 parts by weight of the above defective carbon nanotubes and 60-180 parts by weight of water, ultrasonically treats at an ultrasonic power of 600-1000 W and an ultrasonic frequency of 60-100 kHz for 20-40 min to obtain a dispersion of defective carbon nanotubes, adds 0.5-2 parts by weight of a hydroxy silicon derivative at 50-70° C. and 300-500 rpm, continues stirring for 3-6 hours, suction filters, washes, and vacuum dries to obtain pre-modified carbon nanotubes;

[0030] N3: Mix the pre-modified carbon nanotubes with 80-200 parts by weight of water, ultrasonicate for 50-80 min at an ultrasonic power of 600-1000 W and an ultrasonic frequency of 60-100 kHz, adjust the pH to 10, filter, and dry. Add the dried product to 100-300 parts by weight of dichloromethane and 1-4 parts by weight of a surfactant, and stir at room temperature and 300-500 rpm for 8-14 h; let stand, remove the supernatant, retain the lower suspension, and vacuum dry to obtain modified carbon nanotubes.

[0031] The hydroxy silicon derivative is any one of 3-(trihydroxysilyl)propylmethyl phosphate and 3-(trihydroxysilyl)-propane sulfonic acid.

[0032] The surfactant is any one of coconut oil alkyl dimethyl ethyl benzyl chloride quaternary ammonium salt, nonylphenol polyoxyethylene ether quaternary ammonium salt, and (carboxymethyl) coconut oil alkyl dimethyl ammonium chloride.

[0033] The method for preparing the high-performance metal-based heat-resistant composite material is characterized by comprising the following steps:

[0034] (1) Weigh the corresponding raw materials according to the above formula;

[0035] (2) mixing the reinforcement, copper powder, nickel powder and silver powder, and ball milling at 300-600 rpm for 1-4 h, wherein the mass ratio of the grinding ball to the raw material is (8-12):1, and the ball milling medium is a zirconium ball with a diameter of 0.3-1 mm, to obtain a mixed powder;

[0036] (3) adding the mixed powder into a pressing mold, pressing the pressed embryo at a pressure of 18-30 MPa for 0.5-2 min, placing the pressed embryo in an inert gas protection environment, heating it to 750-1000° C. at 3-8° C. / min for calcination for 3-8 h, and cooling it naturally to obtain the high-performance metal-based heat-resistant composite material.

[0037] Beneficial effects of the present invention:

[0038] 1. The present invention provides a method for preparing a high-performance metal-based heat-resistant composite material. The method improves the wettability of the carbon-copper interface by adding a silicon-doped boron quantum dot complex. The effective boron quantum dots and modified carbon nanotubes are effectively combined, each playing the role of heat resistance and mechanical properties. The interface between the modified carbon nanotubes and the Cu matrix generates internal stress, which is conducive to good mechanical bonding between the composite interface. The introduced carbon nanotubes can improve the stability of the boron quantum dots in the metal-based heat-resistant composite material, and the boron quantum dots can be better dispersed in the metal-based composite material because of the combination with the carbon nanotubes, which improves the wettability between the reinforcing phase and the matrix, improves the interface bonding, and is conducive to improving the load transfer efficiency. The two work together to improve the heat resistance and mechanical properties of the metal-based heat-resistant composite material.

[0039] 2. The preparation method of the present invention is simple and reliable, has good repetition rate and high productivity. The prepared silicon-doped boron quantum dot composite has good wettability with metal-based matrix materials and a firm interface bond. It can be used as a reinforcement for composite materials, thus expanding its application range. DETAILED DESCRIPTION

[0040] The above content of the present invention is further described in detail below in conjunction with specific implementation modes, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments.

[0041] Some of the raw materials in the examples herein are introduced as follows:

[0042] Graphitized carbon nanotubes were purchased from Beijing Zhongke Jinyan Technology Co., Ltd., model: CNT223.

[0043] Example 1

[0044] A high-performance metal-based heat-resistant composite material comprises the following raw materials in mass fraction: 75wt% copper powder, 15wt% nickel powder, 3wt% silver powder and 7wt% reinforcement.

[0045] The reinforcement is a boron quantum dot; the preparation method of the boron quantum dot comprises the following steps:

[0046] S1: 10 parts by weight of boron powder and 80 parts by weight of N-methylpyrrolidone were mixed, stirred at 600 rpm for 30 min, and ultrasonicated at an ultrasonic power of 800 W and an ultrasonic frequency of 80 kHz for 60 min to obtain a mixed solution;

[0047] S2: placing the above mixed solution under nitrogen protection, stirring at 180° C. and 600 rpm for 6 hours, cooling to room temperature, centrifuging, washing, and freeze-drying to obtain boron quantum dots.

[0048] The preparation method of the high-performance metal-based heat-resistant composite material is as follows:

[0049] (1) Weigh the corresponding raw materials according to the above formula;

[0050] (2) The reinforcement, copper powder, nickel powder and silver powder are mixed, and ball milled at 400 rpm for 2 h, with the mass ratio of grinding balls to raw materials being 10:1, and the ball milling medium being zirconium balls with a diameter of 0.5 mm, to obtain a mixed powder;

[0051] (3) adding the mixed powder into a pressing mold, pressing the pressed embryo at a pressure of 20 MPa for 1 min, placing the pressed embryo in an inert gas protection environment, heating to 850° C. at 5° C. / min for calcination for 4 h, and naturally cooling to obtain the high-performance metal-based heat-resistant composite material.

[0052] Example 2

[0053] A high-performance metal-based heat-resistant composite material comprises the following raw materials in mass fraction: 75wt% copper powder, 15wt% nickel powder, 3wt% silver powder and 7wt% reinforcement.

[0054] The reinforcement is silicon-doped boron quantum dots; the preparation method of the silicon-doped boron quantum dots comprises the following steps:

[0055] S1: 10 parts by weight of boron powder and 80 parts by weight of N-methylpyrrolidone were mixed, stirred at 600 rpm for 30 min, ultrasonicated at an ultrasonic power of 800 W and an ultrasonic frequency of 80 kHz for 60 min, and then 1 part by weight of 3-(methacryloyloxy)propyltrimethoxysilane was added, and ultrasonicated at an ultrasonic power of 800 W and an ultrasonic frequency of 80 kHz for 4 h to obtain a mixed solution;

[0056] S2: placing the mixed solution under nitrogen protection, stirring at 180° C. and 600 rpm for 6 hours, cooling to room temperature, centrifuging, washing, and freeze-drying to obtain silicon-doped boron quantum dots.

[0057] The preparation method of the high-performance metal-based heat-resistant composite material is as follows:

[0058] (1) Weigh the corresponding raw materials according to the above formula;

[0059] (2) The reinforcement, copper powder, nickel powder and silver powder are mixed, and ball milled at 400 rpm for 2 h, with the mass ratio of grinding balls to raw materials being 10:1, and the ball milling medium being zirconium balls with a diameter of 0.5 mm, to obtain a mixed powder;

[0060] (3) adding the mixed powder into a pressing mold, pressing the pressed embryo at a pressure of 20 MPa for 1 min, placing the pressed embryo in an inert gas protection environment, heating to 850° C. at 5° C. / min for calcination for 4 h, and naturally cooling to obtain the high-performance metal-based heat-resistant composite material.

[0061] Example 3

[0062] A high-performance metal-based heat-resistant composite material comprises the following raw materials in mass fraction: 75wt% copper powder, 15wt% nickel powder, 3wt% silver powder and 7wt% reinforcement.

[0063] The reinforcement is carbon nanotubes; the preparation method of the carbon nanotubes comprises the following steps: 2 parts by weight of graphitized carbon nanotubes, 1 part by weight of sodium nitrate and 0.3 parts by weight of 98wt% concentrated sulfuric acid are mixed, stirred at 0°C and 400rpm for 20min, 20 parts by weight of 20wt% potassium permanganate aqueous solution are added and stirred for 1h; then stirred at 40°C and 100rpm for 30min, 40 parts by weight of water are added; then stirred at 90°C and 100rpm for 30min, 10 parts by weight of 30wt% hydrogen peroxide are added and stirred for 15min, centrifuged, washed and dried to obtain carbon nanotubes.

[0064] The preparation method of the high-performance metal-based heat-resistant composite material is as follows:

[0065] (1) Weigh the corresponding raw materials according to the above formula;

[0066] (2) The reinforcement, copper powder, nickel powder and silver powder are mixed, and ball milled at 400 rpm for 2 h, with the mass ratio of grinding balls to raw materials being 10:1, and the ball milling medium being zirconium balls with a diameter of 0.5 mm, to obtain a mixed powder;

[0067] (3) adding the mixed powder into a pressing mold, pressing the pressed embryo at a pressure of 20 MPa for 1 min, placing the pressed embryo in an inert gas protection environment, heating to 850° C. at 5° C. / min for calcination for 4 h, and naturally cooling to obtain the high-performance metal-based heat-resistant composite material.

[0068] Example 4

[0069] A high-performance metal-based heat-resistant composite material comprises the following raw materials in mass fraction: 75wt% copper powder, 15wt% nickel powder, 3wt% silver powder and 7wt% reinforcement.

[0070] The reinforcing body is a silicon-doped boron quantum dot composite; the preparation method of the silicon-doped boron quantum dot composite comprises the following steps:

[0071] S1: 10 parts by weight of boron powder and 80 parts by weight of N-methylpyrrolidone were mixed, stirred at 600 rpm for 30 min, ultrasonicated at an ultrasonic power of 800 W and an ultrasonic frequency of 80 kHz for 60 min, and then 1 part by weight of 3-(methacryloyloxy)propyltrimethoxysilane was added, and ultrasonicated at an ultrasonic power of 800 W and an ultrasonic frequency of 80 kHz for 4 h to obtain a mixed solution;

[0072] S2: Add 2 parts by weight of carbon nanotubes to the above mixed solution, ultrasonicate for 60 minutes at an ultrasonic power of 800 W and an ultrasonic frequency of 80 kHz, then place it under nitrogen protection, stir it at 180°C and 600 rpm for 6 hours, cool it to room temperature, centrifuge it, wash it, and freeze-dry it to obtain a silicon-doped boron quantum dot complex.

[0073] The preparation method of carbon nanotubes comprises the following steps: mixing 2 parts by weight of graphitized carbon nanotubes, 1 part by weight of sodium nitrate and 0.3 parts by weight of 98 wt% concentrated sulfuric acid, stirring at 0°C and 400 rpm for 20 minutes, adding 20 parts by weight of a 20 wt% potassium permanganate aqueous solution and continuing to stir for 1 hour; stirring at 40°C and 100 rpm for 30 minutes, adding 40 parts by weight of water; stirring at 90°C and 100 rpm for 30 minutes, adding 10 parts by weight of a 30 wt% hydrogen peroxide solution, continuing to stir for 15 minutes, centrifuging, washing and drying to obtain carbon nanotubes.

[0074] The preparation method of the high-performance metal-based heat-resistant composite material is as follows:

[0075] (1) Weigh the corresponding raw materials according to the above formula;

[0076] (2) The reinforcement, copper powder, nickel powder and silver powder are mixed, and ball milled at 400 rpm for 2 h, with the mass ratio of grinding balls to raw materials being 10:1, and the ball milling medium being zirconium balls with a diameter of 0.5 mm, to obtain a mixed powder;

[0077] (3) adding the mixed powder into a pressing mold, pressing the pressed embryo at a pressure of 20 MPa for 1 min, placing the pressed embryo in an inert gas protection environment, heating to 850° C. at 5° C. / min for calcination for 4 h, and naturally cooling to obtain the high-performance metal-based heat-resistant composite material.

[0078] Example 5

[0079] A high-performance metal-based heat-resistant composite material comprises the following raw materials in mass fraction: 75wt% copper powder, 15wt% nickel powder, 3wt% silver powder and 7wt% reinforcement.

[0080] The reinforcing body is a silicon-doped boron quantum dot composite; the preparation method of the silicon-doped boron quantum dot composite comprises the following steps:

[0081] S1: 10 parts by weight of boron powder and 80 parts by weight of N-methylpyrrolidone were mixed, stirred at 600 rpm for 30 min, ultrasonicated at an ultrasonic power of 800 W and an ultrasonic frequency of 80 kHz for 60 min, and then 1 part by weight of 3-(methacryloyloxy)propyltrimethoxysilane was added, and ultrasonicated at an ultrasonic power of 800 W and an ultrasonic frequency of 80 kHz for 4 h to obtain a mixed solution;

[0082] S2: Add 2 parts by weight of modified carbon nanotubes to the above mixed solution, ultrasonicate for 60 minutes at an ultrasonic power of 800 W and an ultrasonic frequency of 80 kHz, then place it under nitrogen protection, stir it at 180°C and 600 rpm for 6 hours, cool it to room temperature, centrifuge it, wash it, and freeze-dry it to obtain a silicon-doped boron quantum dot complex.

[0083] The method for preparing the modified carbon nanotubes comprises the following steps:

[0084] N1 2 parts by weight of graphitized carbon nanotubes, 1 part by weight of sodium nitrate, and 0.3 parts by weight of 98 wt% concentrated sulfuric acid were mixed, stirred at 0°C and 400 rpm for 20 min, 20 parts by weight of 20 wt% potassium permanganate aqueous solution were added, and stirring was continued for 1 h; then stirred at 40°C and 100 rpm for 30 min, 40 parts by weight of water were added; then stirred at 90°C and 100 rpm for 30 min, 10 parts by weight of 30 wt% hydrogen peroxide were added, stirring was continued for 15 min, centrifuged, washed, and dried to obtain defective carbon nanotubes;

[0085] N2 takes 1 part by weight of the above defective carbon nanotubes and 80 parts by weight of water, ultrasonically treats at an ultrasonic power of 800 W and an ultrasonic frequency of 80 kHz for 30 min to obtain a dispersion of defective carbon nanotubes, adds 1 part by weight of 3-(trihydroxysilyl)propylmethyl phosphate at 60° C. and 400 rpm, continues stirring for 4 h, filters, washes, and vacuum-dries to obtain pre-modified carbon nanotubes;

[0086] N3 The pre-modified carbon nanotubes were mixed with 100 parts by weight of water, ultrasonicated for 60 min at an ultrasonic power of 800 W and an ultrasonic frequency of 80 kHz, the pH was adjusted to 10, filtered, and dried. The dried product was added to 200 parts by weight of dichloromethane and 2 parts by weight of coconut oil alkyl dimethyl ethyl benzyl chloride quaternary ammonium salt, and stirred at room temperature and 400 rpm for 10 h; allowed to stand, the supernatant was removed, the lower suspension was retained, and vacuum dried to obtain modified carbon nanotubes.

[0087] The preparation method of the high-performance metal-based heat-resistant composite material is as follows:

[0088] (1) Weigh the corresponding raw materials according to the above formula;

[0089] (2) The reinforcement, copper powder, nickel powder and silver powder are mixed, and ball milled at 400 rpm for 2 h, with the mass ratio of grinding balls to raw materials being 10:1, and the ball milling medium being zirconium balls with a diameter of 0.5 mm, to obtain a mixed powder;

[0090] (3) adding the mixed powder into a pressing mold, pressing the pressed embryo at a pressure of 20 MPa for 1 min, placing the pressed embryo in an inert gas protection environment, heating to 850° C. at 5° C. / min for calcination for 4 h, and naturally cooling to obtain the high-performance metal-based heat-resistant composite material.

[0091] Test Example 1

[0092] Tensile strength performance test: Referring to the national standard GB / T 32498-2016 "Room temperature test method for tensile test of metal matrix composite materials", the high-performance metal matrix heat-resistant composite materials prepared in Examples 1-5 were first processed into rod-shaped specimens with a specimen size of 5 mm in diameter and 15 mm in length. The processed specimens were tested, with 5 groups tested in each group and the average value taken. The test results are shown in Table 1.

[0093] Impact toughness performance test: Referring to the national standard GB / T 229-2020 "Charpy Pendulum Impact Test Method for Metallic Materials", the high-performance metal-based heat-resistant composite materials prepared in Examples 1-5 were first processed into specimens with a length of 55 mm and a cross-section of 10 mm*10 mm. A V-shape was set in the middle of the specimen. Five groups were tested in each group, and the average value was taken. The test results are shown in Table 1.

[0094] Table 1 Mechanical properties test results

[0095] Tensile strength MPa <![CDATA[Impact toughness J / cm 2 > Example 1 413 18 Example 2 428 20 Example 3 483 27 Example 4 516 30 Example 5 542 32

[0096] Test Example 2

[0097] Thermal expansion coefficient performance test: Referring to the national standard GB / T4339-2008 "Determination of thermal expansion characteristic parameters of metal materials", the high-performance metal-based heat-resistant composite materials prepared in Examples 1-5 were tested, 5 groups were tested in each group, and the average value was taken. The test results are shown in Table 2.

[0098] Table 2 Thermal expansion coefficient performance test results

[0099] <![CDATA[Coefficient of thermal expansion × 10 -6 m / K]]> Example 2 0.83 Example 3 1.9 Example 5 0.13

[0100] The high-performance metal-based heat-resistant composite material prepared by the present invention has good mechanical properties and heat resistance. Comparing Examples 1-2, the reason is that the introduction of silicon can adjust the structure of quantum dots and increase their interaction with the metal matrix, thereby improving the overall mechanical properties of the material. The high hardness of silicon-doped boron quantum dots can effectively resist deformation and wear of the material under high temperature and high stress environments. This is helpful for better dispersing and transferring heat in a high temperature environment, slowing down the temperature rise of the material, and improving its heat resistance.

[0101] Comparing Examples 3-5, Example 5 is compared with Example 4. The carbon nanotubes are directly added to the copper matrix. Due to the difference in the intrinsic properties of the carbon nanotubes and the matrix, it is difficult to control the spatial distribution of the reinforcement, resulting in unsatisfactory mechanical and heat resistance properties of the composite material. However, Example 5 adds modified carbon nanotubes to form a high-performance metal-based heat-resistant composite material with excellent performance. The modified carbon nanotubes are fluid-like, so that the copper-based material and the silicon-doped boron quantum dots can be firmly combined through the B-Si-C-Cu bond during the pressing and calcining steps, and the silicon-doped boron quantum dots can be evenly dispersed in the copper-based material. In the subsequent processing and use process, the problem of distribution segregation of quantum dots can be reduced, and the use efficiency and stability are greatly improved. The problems of poor uniform dispersion of carbon nanotubes, poor C-Cu interface bonding, uncertain orientation of carbon nanotubes, and poor density of composite materials are overcome. It can not only effectively combine with boron quantum dots to improve the interface bonding performance with the metal matrix, but also improve the bending strength, tensile strength, hardness, toughness and thermal conductivity of the material, so that the composite material can better resist the load under high temperature and high stress environment, reduce the risk of cracks and fractures under high stress, and can also significantly improve the thermal conductivity of metal-based composite materials.

[0102] As can be seen from Examples 2-4, the effective boron quantum dots and modified carbon nanotubes of the present invention are effectively combined, each playing the role of heat resistance and mechanical properties, and the interface of the modified carbon nanotubes and the Cu matrix produces internal stress, which is conducive to good mechanical bonding between the composite interface. The introduced carbon nanotubes can improve the stability of boron quantum dots in metal-based heat-resistant composite materials, and boron quantum dots can be better dispersed in metal-based composite materials because they are combined with carbon nanotubes, which improves the wettability between the reinforcing phase and the matrix, improves the interface bonding, and is conducive to improving the load transfer efficiency. The two work together to improve the heat resistance and mechanical properties of metal-based heat-resistant composite materials.

Claims

1. A high-performance metal-based heat-resistant composite material, characterized in that: The invention comprises the following raw materials in mass fraction: 70-85wt% copper powder, 5-20wt% nickel powder, 1-5wt% silver powder and 5-10wt% reinforcing body, wherein the reinforcing body is silicon-doped boron quantum dots or silicon-doped boron quantum dot composite.

2. The high performance metal-based heat-resistant composite material according to claim 1, characterized in that: The method for preparing silicon-doped boron quantum dots comprises the following steps: S1: mixing boron powder and N-methylpyrrolidone, stirring, ultrasonicating, and then adding a silane coupling agent and ultrasonicating to obtain a mixed solution; S2: placing the above-mentioned mixed solution under nitrogen protection for hydrothermal reaction to obtain silicon-doped boron quantum dots.

3. The high performance metal-based heat-resistant composite material according to claim 1, characterized in that: The preparation method of the silicon-doped boron quantum dot composite is as follows: S1: mixing boron powder and N-methylpyrrolidone, stirring, ultrasonicating, and then adding a silane coupling agent and ultrasonicating to obtain a mixed solution; S2: adding modified carbon nanotubes to the above mixed solution and subjecting it to ultrasonic treatment, and then subjecting it to hydrothermal reaction under nitrogen protection to obtain a silicon-doped boron quantum dot composite.

4. The high performance metal-based heat-resistant composite material according to claim 2 or 3, characterized in that: The silane coupling agent is any one of 3-(methacryloyloxy)propyl trimethoxysilane, diethylenetriaminopropyl trimethoxysilane and 3-glycidyloxypropyl trimethoxysilane.

5. The high performance metal-based heat-resistant composite material according to claim 3, characterized in that: The method for preparing the modified carbon nanotubes comprises the following steps: N1: graphitized carbon nanotubes, sodium nitrate and concentrated sulfuric acid are mixed and stirred, and potassium permanganate aqueous solution is added and stirred continuously; heating is performed for reaction, and hydrogen peroxide is added and stirred continuously to obtain defective carbon nanotubes; N2 takes the above defective carbon nanotubes and water and ultrasonically obtains a dispersion of defective carbon nanotubes, and adds a hydroxy silicon derivative under heating and stirring to obtain pre-modified carbon nanotubes; N3: Mix the pre-modified carbon nanotubes with water, disperse them by ultrasonic, filter and dry them, add the dried product into dichloromethane and surfactant and stir; let it stand, remove the upper clear liquid, retain the lower suspension, and dry it in vacuum to obtain modified carbon nanotubes.

6. The high performance metal-based heat-resistant composite material according to claim 5, characterized in that: The hydroxy silicon derivative is any one of 3-(trihydroxysilyl)propylmethyl phosphate and 3-(trihydroxysilyl)-propane sulfonic acid.

7. The high performance metal-based heat-resistant composite material according to claim 5, characterized in that: The surfactant is any one of coconut oil alkyl dimethyl ethyl benzyl chloride quaternary ammonium salt, nonylphenol polyoxyethylene ether quaternary ammonium salt, and (carboxymethyl) coconut oil alkyl dimethyl ammonium chloride.

8. The method for preparing a high-performance metal-based heat-resistant composite material according to any one of claims 1 to 7, characterized in that: The steps include: (1) Weigh the corresponding raw materials according to the above formula; (2) mixing the reinforcement, copper powder, nickel powder and silver powder and ball milling to obtain a mixed powder; (3) adding the mixed powder into a pressing mold to press the embryo, placing the pressed embryo in an inert gas protection environment for calcining, and cooling naturally to obtain the high-performance metal-based heat-resistant composite material.

Citation Information

Patent Citations

  • High-thermal-conductivity composite material and preparation method thereof

    CN117187617A

  • Preparation method and applications of boron quantum dots

    CN110194464A

  • Copper-based self-lubricating composite material and preparation method thereof

    CN114000007A